PENGARUH SUMBER DAYA TERHADAP KINERJA PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KETAPANG - Annisaa E42009023, Ghanis Ayu (FISIP Universitas Tanjungpura Pontianak, 2013)
This thesis aims for knowing there is or not influence resource against service performance on population administration in Department of Population and Civil Registration Regency of Ketapang. The title of thesis is determined based on the problems which identified by researchers namely the slow pace service performance on population administration in Department of Population and Civil Registration Regency of Ketapang.Â This study uses a combination of research methods (Sequential Explanatory Design), is to perform data collection and analysis of quantitative data in the first stage, and was followed by data collection and analysis of qualitative data in the second stage, in order to strengthen the results of quantitative research conducted in the first phase. The study was conducted through hypothesis testing. The result is a significant difference between the performance of the resource population administration services in the Department of Population and Civil Registration Ketapang District, in the amount of 43.16% and a correlation coefficient was strong.Â Keywords: Resource, Service Performance.